Parenting Support in England: The Bedding Down of a New Policy. Issue 4 (3rd June 2015) - Daly, Mary; Bray, Rachel
<x content-type="archive" xml:space="preserve">Abstract</x> This article enquires into how parenting support, as concept, policy and provision, has penetrated the English social policy landscape, and critically considers why it has proved so popular with policy makers. It first outlines the existing policy configuration. The second section identifies some key factors precipitating the roll-out of parenting support and the third section takes an overview of the significance of the developments from a social and family policy perspective. The argument advanced is that the growth and expansion of parenting support is explained by a coming together of a set of political exigencies around 'risk' and the healthy child, and a set of policy 'solutions' which are seen to have high promise. In particular, parenting support has the advantage of being relatively easily generalisable (especially in the form of programmes) and aligns with several current developments of the welfare state, towards activation, provision of support through services and an interest in localism.